Management accounting development in response to organizational environmental changes - Gholami, Asef; Kordestani, Gholamreza; Ramezani Sarajari, Haniyeh (International Journal of Business Management and Entrepreneurship, 2025)
Management accounting, as a key subfield of accounting, has always been influenced by environmental changes, continuously evolving to meet managerial and organizational needs. This paper examines the relationship between modern management accounting techniques and environmental and organizational transformations, with a focus on the transformative role of information technology in this field. Based on an analysis of information gathered from articles, books, online resources, and search engines, this study presents a framework that highlights the need to reform traditional management accounting systems, identifies future trends and directions, and explores the changing role of management accountants. Furthermore, we conducted a study of the status of management accounting and accountants in Iran, examining key aspects such as the present state, barriers and challenges to development, the impact of startups on the transformation of management accounting, and the evolving role of management accountants. The findings indicate that in the era of information and knowledge-based economies, achieving a balance between technical skills and broad-based knowledge is crucial for adapting to ongoing changes. Ultimately, understanding management accounting practices at both local and global levels can enhance organizations’ competitive advantage.